Black Ice: David Blackwood Prints of Newfoundland. THE ART GALLERY OF ONTARIO, TORONTO - VanderBerg, Robert (Archivaria, 2011)
Black Ice: David Blackwood Prints of Newfoundland. THE ART GALLERY OF ONTARIO, TORONTO. Mounted at the Art Gallery of Ontario, 5 February–12 June 2011.